The Assessment of the Possibility of Using Ethanol and Ultrasound to Design the Properties of Dried Carrot Tissue - Magdalena Dadan; Malgorzata Nowacka (Applied Sciences, 2021)
The purpose of this study was to investigate the effect of pre-treatment in ethyl alcohol for 5, 15, 60 and 180 s with the application of ultrasound on the course of convective drying and properties of carrot tissue directly after the treatment and after the drying process. The treatment in ethanol resulted in loss of mass, increase of dry matter, ethanol conductivity, extractivity of carotenoids with a slight effect on the colour of carrot tissue after the treatment. The utilization of ultrasound during immersion in ethanol contributed to additional increase of conductivity of ethanol, and extractivity of carotenoids. The immersion in ethanol virtually did not affect the drying kinetics, which can be explained by the increase of shrinkage of the tissue in relation to the untreated dried tissue. Despite the lack of the influence on the drying course in the ethanol-immersed carrot, an increase of the carotenoid content (up to 135%) and the rehydration ability (up to 19%) was noted with the simultaneously unchanged colour of dried carrot in comparison to untreated dried material, which indicates the possibility to improve the quality of dried carrot after immersion in ethanol.